Occurrence and antimicrobial profiling of K. pneumoniae in burn patients at burn ward, Allied Hospital, Faisalabad - M Usman Qaisar, M. Aamir Aslam, Kaleem Ullah, Rabia Kanwar, Saqib Ali, Ifra Farzand, Zain Mehmood, Ammar Hussain, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Klebsiella pneumonia is an opportunistic pathogen causing a great array of illness both in humans and animals and responsible for high mortality rate in burn patients. Aim: To determine occurrence of K. pneumonia in burn wound patients and to check antibiotic sensitivity of K. pneumoniae. Methods: A retrospective cross sectional study was conducted and 50 samples of burn wound patients from Allied Hospital Faisalabad were taken for isolation, identification and antibiotic resistance pattern of K. pneumonia. Samples then inoculated on MacConkey agar for pure colonies. For identification gram staining and biochemical test were performed. Kirby-Bauer disk diffusion technique was used to determined antibiotic sensitivity profiling K.pneumoniae against various disks. Results: On MacConkey agar mucoid, lactose fermenting pink colonies of K. pneumoniae were observed. Among the biochemical tests, catalase, citrate and VP test were found to be positive whereas indole and methyl red tests were found to be negative. Occurrence of K. pneumoniae was 28% in burn patients. Antibiotic sensitivity profiling showed that K. pneumonia was found highly sensitive to Imipenem (88.94%), meropenem (79.32%), ertapenem (75%), moderately sensitive to aminoglycoside group (amikacin 59.13%, gentamicin 52.40%, Netilmicin 50.96%), piperacillin-tazobactam (53.84%) mildly sensitive to tobramycin (49.51%), nitrofurantoin (48.07%), levofloxacin (45.19%) Conclusion: K. pneumoniae and other gram negative bacilli are frequently associated with nosocomial burn infection. Furthermore, most isolates of K. pneumoniae from burn units were MDR K. pneumonia. Keywords: Opportunistic pathogen, Antibiotic sensitive, Burn, Mortality, Nosocomial.